RANCANGAN PROGRAM PELATIHAN UNTUK MENINGKATKAN SELF EFFICACY NEGOSIASI PADA SISWA SMK - Syarvia Syarvia (Psympathic : Jurnal Ilmiah Psikologi, 2014)
This research aimed to develop a training design to increase self-efficacy on negotiation for students of vocational school. Research subjects were 18 students of the SMK 1 Bandung class of 2011 marketing majoring. The design of the training program was conceived and developed with reference to the strength aspect of self-efficacy and negotiation, by applying the model of experiential learning. The training material organized into two main activities to improve selfefficacy in negotiation namely our business and making a profit. The effectiveness of the training is measured by the increase of self-efficacy category by using an instrument on negotiation selfefficacy, behavioral observation and evaluation of training. This study used a quasi-experimental method with the untreated control group pretest and posttest sample dependent design. T-Test results showed there’s no significant improvement in the category of self-efficacy negotiations after the training program. Quantitatively and observations during training showed an increase in self-efficacy negotiation in aspects of communication, strategy and relationships, as well as a decrease in the emotional aspects among training participants.